Clinical Characteristics and Outcome of Diabetic Ketoacidosis: Experience at BIRDEM, Dhaka, Bangladesh (Bangladesh Critical Care Journal, 2015)
Background: Diabetic ketoacidosis (DKA) is a medical emergency. It may be the presenting feature of diabetes mellitus, but more commonly DKA complicates diabetic patients during inter-current acute illness or if they become non-compliant to anti-diabetic medications. Early detection and treatment of DKA including underlying cause is important in determining outcome.Objectives: To describe the demographic characteristics, presentations, precipitating factors and outcome of DKA.Methods: This cross-sectional study was conducted at BIRDEM General Hospital from January 2008 to December 2011.Results: Total patients were 200 with female predominance (56%). Mean age of the study population was 37.6 years. Incidence of DKA was more in known diabetic patients (71%) than in new cases (29%), more among rural population (53%) and low income group (76.5%). Common presentations included nausea (63%), vomiting (61%), polyuria (43%), polydypsia (42.5%), fever (29%), abdominal pain (28%), shortness of breath (28%), drowsiness (20%), blurred vision (13%), leg cramps (6.5%) and coma (7%). Infection (45.5%) was the commonest precipitating cause of DKA followed by non-adherence to insulin therapy (31%). Acute pancreatitis (5%), myocardial infarction (2%), stroke (1%) and surgery (1.5%) were less common precipitating factors. Aetiology of DKA could not be identified in 14% cases. Mean random blood glucose during admission was 27.1mmol/L and mean HbA1c was 11.3%. Severe acidosis (pH